Post-traumatic, Depression, Anxiety, and Stress Symptoms among Malaysian Firefighters - Abdul Azis, Huwaida; A Rahman, Zairina; A Rashid, Mohd Radzniwan; Baharom, Nizam; Awang, Hamidin; Mohammad Lukman, Nur Hafizah; Zainal Abidin, Mohd Zairi (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Emergency responders, including firefighters are frequently exposed to life-threatening situations in their daily lives causing an increased risk for occupational stress, anxiety, depression and post-traumatic stress symptoms (PTSS). Hence, this study aimed to determine the prevalence, and correlation of PTSS with stress, anxiety, and depression among Malaysian firefighters. MATERIALS AND METHODS: A cross-sectional study was conducted among firefighters stationed in 20 fire and rescue stations in Penang, Malaysia using self-administered online survey through a purposive sampling. Information collected were sociodemographic data, measurement of severity of PTSS via Post-Traumatic Checklist-5 (PCL-5), and assessment of depression, anxiety, and stress via Depression, Anxiety, and Stress Scale (DASS-21). A descriptive analysis and Pearson’s correlation coefficient analyses were employed in study analysis. RESULTS: Out of 562 firefighters participated in the study, the prevalence of PTSS, stress, anxiety, and depression was 5.0%, 2.1%, 13.0%, and 8.5%, respectively. Among those with PTSS, 28.6%, 78.6%, and 67.9% suffered from stress, anxiety, and depression, respectively. Hence, anxiety was highly coexisted with PTSS. There was significant positive correlation between PTSS score and the score of stress (r=0.656, P< 0.001), anxiety (r=0.699, P< 0.001), and depression (r=0.700, P< 0.001). CONCLUSION: Our study findings suggested that stress, anxiety, and depression can co-occur with PTSS. Hence, firefighters should have regular mental health assessments as the concurrent effect of multiple medical conditions may require comprehensive treatment to address the various aspects of each condition.